Pengaruh Gaya Kepemimpinan Transformasional, Budaya Organisasi Dan Kompentensi Terhadap Motivasi Dan Kinerja Guru - Hitu Iphank, Faripa La; Rraka Ardiana, I Dewa Ketut (Media Mahardhika, 2017)
This study aimsto determine the effect of transformational leadership style, organizational culture and motivation competence and their impact onthe performance ofa high school teacherin Taliabu Island. This study aimsto determine the effect of transformational leadership style, organizational culture and motivation competence and their impact onthe performance ofa high school teacher indirect Taliabu. The population inthis studyall teachers of high schools in taliabu using saturated sample, in which all members of the sampled population numbering 103 people. The data analysis used in this study is to test the validity of using Product Moment Correlation and reliability testing using Alpha Crobach and analyzed by using Partial Least Square (PLS). The results showed that: 1) there is no significant relationship between transformational leadership and teacher at the high school performance Taliabu. 2) there is no significant relationship between organizational culture and performance of State in Taliabu. 3) there isa positiveand significant relationship between competence and emotional intelligence on the performance ofhigh school in Taliabu. 4) there isa significant and positive effect between transformational leadership style, employee motivation of teachers to high schools in Taliabu. 5) there isa positive and significant influence between organizational culture and motivation of high school teachers in Taliabu. 6) there is no significant relationship between competence and motivation of high school teacher in Taliabu.7) there isa significantand positive influence between work motivation of teachers and high school teachers in Taliabu performance. Based on these resultsit can be concluded, transformational leadership, organizational culture does not significantly influence the performance of teachers in Taliabu high school. Transformational leadership style and organizational culture have positive effect on the motivation of teachers work in the high school district of the Taliabu island.